2011
DOI: 10.1017/s0030605310001080
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of primates reveals Samkos Wildlife Sanctuary, Cardamom Mountains, Cambodia as a priority area for conservation

Abstract: We conducted a primate survey in Samkos Wildlife Sanctuary, western Cambodia, during the wet season in 2009. We visually confirmed the presence of five out of six primate species thought to occur in the area: Bengal slow loris Nycticebus bengalensis, Indochinese silvered langur Trachypithecus germaini, pileated gibbon Hylobates pileatus, pig-tailed macaque Macaca leonina and long-tailed macaque Macaca fascicularis. We did not find any sign of the stumptailed macaque Macaca arctoides and suggest it is absent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Earlier studies (Charles-Dominique & Bearder, 1979) suggested that nocturnal primates reduce their activity during the middle period of the night. However, our results are in accordance with other work on the genus Nycticebus , suggesting that these animals are active throughout the night, with the exception of periods of torpor (Starr et al, 2010; Coudrat et al, 2011). Bengal slow lorises were most often found in trees of the genus Terminalia (Combretaceae), from which they are known to consume both leaves and gum (Swapna et al, 2009; Rogers & Nekaris, 2011; Das, pers.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies (Charles-Dominique & Bearder, 1979) suggested that nocturnal primates reduce their activity during the middle period of the night. However, our results are in accordance with other work on the genus Nycticebus , suggesting that these animals are active throughout the night, with the exception of periods of torpor (Starr et al, 2010; Coudrat et al, 2011). Bengal slow lorises were most often found in trees of the genus Terminalia (Combretaceae), from which they are known to consume both leaves and gum (Swapna et al, 2009; Rogers & Nekaris, 2011; Das, pers.…”
Section: Discussionsupporting
confidence: 93%
“…Surveys were also conducted in communities surrounding the Central Cardamom Mountains National Park, part of a large protected landscape in southwest Cambodia, which harbours a potentially regionally significant population of sun bears [38]. Currently, there is evidence to suggest that Stung Treng and the Cardamom Mountains may be “source” sites of illegal animals and animal parts [39, 40].…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of the distribution, abundance and status of Cambodian wildlife is limited (Coudrat et al 2011), although at least 12 species of primates are found across the country (Table 1.3) (Rawson & Roos 2008;Nadler et al 2010). However, like other primates around the world, Cambodian primates are now under threat (Nadler et al 2010) (Table 1.3).…”
Section: Cambodian Primatesmentioning
confidence: 99%
“…However, like other primates around the world, Cambodian primates are now under threat (Nadler et al 2010) (Table 1.3). Illegal logging, deforestation, agricultural development, hunting, illegal trade, mine development, and poor law enforcement all contribute to declining primate populations (Coudrat et al 2011;Starr et al 2011). Cambodian Primates are among the most poorly studied wild animals in Cambodia, with only a few species having been studied, such as the genera Nomascus (Frechette 2014;Nelson 2014;Frechette et al in prep), Nycticebus, and Hylobates (Konrad 2004;Traeholt et al 2006;Rawson & Roos 2008;Coudrat et al 2011;Starr et al 2011).…”
Section: Cambodian Primatesmentioning
confidence: 99%